Spitzenfußball und Globalisierung - Thiel, A.; Riedl, L.; Cachay, K. (Leipziger Sportwissenschaftliche Beiträge, 2005)
Despite the fact that global structures in top sports had already existed since the beginning of the 20th century, a strong national tendency was noticeable for a long time. However, processes of globalisation in the mid-nineties reduced the importance of the criteria of nationality significantly. The reasons were the change in entry conditions to the European club competitions on the one hand and, on the other hand, the so-called Bosman decision (1995), which declared invalid the restrictions in place at that time for foreigners for national associations. Sports clubs now had the opportunity to bring virtually as many foreign players into action as desired. In order to remain internationally competitive, the clubs had to recruit their players on the global market and try to solve the problem of world-wide market scouting with specific informational structures and methods. Considering the relation of the audience to the club, it surprisingly shows that the spectators can easily identify with multicultural squads, and that the nationality of players is rather unimportant. Thus, the distinctive criteria for the goodwill of the audience are rather the performance of the players and their commitment to their club.